2016
DOI: 10.1155/2016/8745972
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intestinal Ultrasound on Classification and Management of Crohn’s Disease Patients with Inconclusive Colonoscopy

Abstract: Background and Aims. We aim to evaluate the benefit of ultrasound in the assessment of Crohn's disease and to demonstrate its potential contribution to disease management. Methods. We conduct a retrospective review of adult patients with Crohn's disease examined with sonography and colonoscopy within 30 days. Study patients were identified in whom colonoscopy did not access a pathological segment, detected and evaluated by ultrasonography. Changes in management were predominantly attributed to ultrasound in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…There were no cases where the distal terminal ileum was normal on endoscopy and disease was isolated to the proximal small bowel, as has been reported in up to 30% of cases with small bowel involvement [30]; however, in 2 patients with both US and endoscopic activity (true positives), there was an estimation between 25 and 30 cm of active disease proximal to that region examined endoscopically. Thus, US also provided insight into the length or burden of the disease [31]. One case exhibited negative US and negative endoscopy, yet mild inflammatory activity on pathology.…”
Section: Discussionmentioning
confidence: 99%
“…There were no cases where the distal terminal ileum was normal on endoscopy and disease was isolated to the proximal small bowel, as has been reported in up to 30% of cases with small bowel involvement [30]; however, in 2 patients with both US and endoscopic activity (true positives), there was an estimation between 25 and 30 cm of active disease proximal to that region examined endoscopically. Thus, US also provided insight into the length or burden of the disease [31]. One case exhibited negative US and negative endoscopy, yet mild inflammatory activity on pathology.…”
Section: Discussionmentioning
confidence: 99%
“…The actual research data suggests that intestinal US has a pivotal role in monitoring CD and response to therapy [31,39,40,[66][67][68]. There are yet few studies concerning this subject, but the results are promising.…”
Section: Monitoringmentioning
confidence: 99%
“…Few would disagree that radiologists require specific training when evaluating the small bowel for CD, although it is unclear whether this is greater for US than for MRI, as is commonly supposed. There is in fact few data evaluating training requirements for competency in SBUS, although learned bodies (for example, European gastroenterologists) have produced detailed curriculums and advice on learning strategies . With respect to MRE, one study investigating formal training with direct case‐by‐case feedback in 31 inexperienced readers concluded that experience of at least 100 cases was required to achieve the acceptable MRE activity grading accuracy of 75% …”
Section: Small Bowel Us Vs Mr Enterography In CDmentioning
confidence: 99%
“…111 Interestingly, SBUS disclosed active disease in up to 52% of patients asymptomatic on follow up. 111,112 Wilkens et al 113 retrospectively reviewed 115 CD patients having comprehensive ultrasound and colonoscopy within 30 days of each other. Seventy-four patients (64%) had disease matched on the two tests but 41 (36%) patients demonstrated abnormal bowel on US alone, proximal to the reach of ileocolonoscopy (although of these only eight had disease confirmed by subsequent surgery: the remainder had no corroborative test).…”
Section: Impact On Managementmentioning
confidence: 99%
See 1 more Smart Citation